The ruined wife eaudiobook Psychological thriller. - Montgomery, Marin (Tantor Media, 2019)
Alastair has found the perfect partner in husband, Steven. Together they've built a successful life, had a beautiful child, and still behave like newlyweds long since the day he carried her over the threshold. But all of that changes in an instant thanks to a thoughtless deed that has lifelong repercussions. With secrets bubbling to the surface, the pair find their American dream life suddenly in jeopardy, and neither one of them are willing to let go at any cost.